The effect of midwifery led counseling based on Gamble’s approach on childbirth fear and self-efficacy in nulligravida women - Laya Firouzan; Roghieh Kharaghani; Saeedeh Zenoozian; Reza Moloodi; Elham Jafari (BMC Pregnancy and Childbirth, 2020)
Abstract Background Studies show that childbirth fear is a common problem among Iranian women. Therefore, most Iranian women prefer caesarean section for giving birth. This study investigated the effectiveness of a psychoeducational intervention by midwives (birth emotions - looking to improve expectant fear (BELIEF)) on decreasing childbirth fear and self-efficacy among first-time pregnant women who were afraid of giving birth. Methods A number of 80 pregnant women participated in the study. They had received a score of ≥66 on the Wijma delivery expectancy/experience questionnaire. They were randomly assigned into two groups: intervention (n = 40) and control groups (n = 40). The intervention group received two face-to-face counseling sessions based on the BELEF protocol in the 24th and 34th weeks of pregnancy. Between these two sessions, it also received eight telephone-counseling sessions once a week. The control group only received the prenatal routine care. The outcome measures were childbirth fear, childbirth self-efficacy, and childbirth preference. Results The intervention group showed significantly more reduction in childbirth fear and more increase in childbirth self-efficacy compared to the control group. In addition, more women in the intervention group reported that they preferred to give normal vaginal birth than women in the control group. Conclusion The BELIEF protocol could be an effective approach in reducing childbirth fear and increasing childbirth self-efficacy among first-time pregnant women who are afraid of giving birth. Trial registration number IRCT20101219005417N3, Date of Registration: 19-12-2018.